2009
DOI: 10.1590/s1984-82502009000200018
|View full text |Cite
|
Sign up to set email alerts
|

Drug-related problems observed in a pharmaceutical care service, Belo Horizonte, Brazil

Abstract: This present observational, longitudinal, and non-concurrent study was developed with the purposes of evaluate the profile of patients attended by a pharmacotherapeutic follow-up service and describe the Drug-Related Problems (DRPs) found over there; determine the proportion of DRPs between the health problems presented by the studied population, classifying them and identifying the situations related with their appearance. The study was developed at the School Pharmacy of Newton Paiva University Center, Belo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
3
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 15 publications
3
15
3
3
Order By: Relevance
“…This result is consistent with a number of studies [25,[29][30][31][32][33] on DTPs in which dosing and/or drug selection problems and drug interaction were identified among the major forms of DTPs encountered.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result is consistent with a number of studies [25,[29][30][31][32][33] on DTPs in which dosing and/or drug selection problems and drug interaction were identified among the major forms of DTPs encountered.…”
Section: Discussionsupporting
confidence: 91%
“…Although Ramalho de Oliveira et al [28] identified 38,631 DTPs over a period of 10 years, ð The denominator was 234 (total DTPs encountered); RI = renal impairment, DTP = Drug-Therapy problem, DI = Dosing inadequacy, Drugs with restrictions (dose adjustment needed in case of renal impairment (RI)) per patient, SD = Standard deviation. [29] in a period of two years, and Root et al [30] identified 88 DTPs from 40 patients. The difference in the number of DTPs encountered is probably due to differences in research design in terms of patients type, hospital types, duration of the studies and nature of data collected.Our study showed that mean drug per patient was almost 3.0 which is moderate, despite the involvement of older population of patients in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inadequate use of medications and difficulty understanding the prescribed posology were among the most frequently identified problems by the pharmacy technicians, which is similar to data reported in previous studies conducted in Brazil [13][14][15][16][17] . Similarities in the packaging of different medications, reduced vision among elderly individuals, illiteracy, an inability to understand the writing of the prescribing physician or the abbreviations employed and complex therapeutic protocols involving different administration times are among the factors that contribute to confusion with regard to the use of medications 18 .…”
Section: Discussionsupporting
confidence: 84%
“…Brazilian studies have already described the difficulty of many patients in understanding the prescribed regimen [28][29][30][31][32] . The understanding of prescription varied in studies conducted in other cities, and according to the methodology, ranging from 34% to 70% 25,26,31 .…”
Section: Discussionmentioning
confidence: 99%